Constructing Neoliberalism : Economic Transformation in Anglo-American Democracies - Swarts, Jonathan, 1970- (Book collections on Project MUSE., 2013)
Constructing Neoliberalism presents a rich analysis of the shift to neoliberal economic policies in four Anglo-American democracies -- Canada, Britain, Australia, and New Zealand -- over the course of the 1980s and 1990s.